Protection Motivation Theory and Intentions to Receive the COVID-19 Vaccine. Issue 3 (May 2023) - Kowalski, Robin M.; Deas, Nicholas; Britt, Noah; Richardson, Emily; Finnell, Sophie; Evans, Kelly; Carroll, Hailey; Cook, Andrew; Radovic, Emily; Huyck, Tanner; Parise, Isabella; Robbins, Chelsea; et al.
Background. Declared a "public health threat of international concern" by the World Health Organization, the COVID-19 virus has caused the deaths of over half a million individuals in the United States in just the first 23 months after detection. The vaccine has recently been introduced to reduce this public health threat. However, due, in part, to the rapidity with which the vaccine was developed, many individuals display vaccine hesitancy. Purpose. The current study examined the utility of the Protection Motivation Theory of Health (PMT) in predicting intentions to receive the COVID-19 vaccine. Method. One hundred twenty-nine unvaccinated respondents (drawn from an initial sample of 255 participants) completed a survey assessing the components of the PMT and intentions to receive the vaccine. Respondents could also provide an open-ended response regarding any concerns they had with the vaccine. Conclusions. The PMT accounted for 76% of the variance in vaccine intentions. Vulnerability, outcome efficaciousness, and maladaptive response rewards each accounted for unique variance. Open-ended responses reflecting concerns with the vaccine fell into 8 categories, with the most common being concern with the long-term side effects of the vaccine. These results suggest that public health campaigns promoting the vaccine should focus on vulnerability to COVID-19, protective functions of the vaccine, and overcoming what people perceive as benefits of not receiving the vaccine.